Alternatif Skema Pembiayaan Dalam Pembangunan Infrastruktur Bandar Udara di Indonesia - Eny Yuliawati (WARTA ARDHIA, 2011)
The availability of infrastructures is very important to support and determine the level of efficiency and effectiveness economy activities of a country. The availability of infrastructures is necessary for development. Thus, at the early stage, infrastructure development in a country is fully supported by the Government through the National Budget. However, along with economy growth of a country, demand on infrastructure service is also increasing. The problem is that those demands are not balanced with government’s ability in providing the infrastructures. Development of air transportation infrastructures has to be done faster in accordance with the increasing number of passengers. Therefore, it is necessary to look at business aspects in order to be feasible and economical. Various chances in model of Public Private Partnerships, project financing and chances in the use of both international proiect financing and domestic capital market for developing airports need to be considered in the future concerning the limited government's ability in financing.